Critical Management Studies in the South African context - A. Goldman, Geoff (Acta Commercii, 2016)
The purpose of the book is to establish the first formalised scholarly work on critical management studies (CMS) in the South African context. The book is a collection of seven chapters, six of which employ a conceptual methodology and one of which follows an interpretive paradigm employing qualitative methods of inquiry. CMS is a relatively young school of thought, arising in the early 1990s and still very much being a peripheral movement within the academic discipline of management. South Africa has very little scholarship on CMS as precious few scholars work in this space. Furthermore, publication opportunities are virtually non-existent as CMS is virtually unknown in the South African community of management scholars. Thus, this book represents the first academic work on CMS published in South Africa, written and reviewed by scholars who are familiar with the field. The primary target readership would be management academics, but it could also be a useful reference for postgraduate students in management. A digital similarities index report confirms the originality of the work and that it has not been plagiarised or published elsewhere.